2000
DOI: 10.1080/00016480060203334
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Expression Correlates with p53 Mutation and Angiogenesis in Squamous Cell Carcinoma of the Head and Neck

Abstract: Vascular endothelial growth factor (VEGF) has potent angiogenic activity and has been identified in a wide variety of malignancies, including head and neck squamous cell carcinoma (HNSCC). The tumour-suppressor gene p53 has been thought to regulate VEGF. Cryostat sections of 33 head and neck squamous cell carcinomas (HNSCC) were immunostained for VEGF using a standard streptavidin-biotin complex procedure. To evaluate angiogenesis, microvascular density was counted by staining endothelial cells immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…This accrued a convincing evidence reported in our study concerning the association of VEGF over expression with the MvD. Similar strong correlation was shown in other studies in oral SCC ( 23,24).…”
Section: Discussionsupporting
confidence: 93%
“…This accrued a convincing evidence reported in our study concerning the association of VEGF over expression with the MvD. Similar strong correlation was shown in other studies in oral SCC ( 23,24).…”
Section: Discussionsupporting
confidence: 93%
“… 27 Though PTGS2 expression was found to be higher in TP53 mutant cells, clinically, no correlation has been found between the two factors in disease progression and survival. 28 Several studies support the hypothesis that p53 regulates the angiogenesis process via the expression of VEGF 29 ; parallelly, in this study, a similar expression pattern was observed where the expression of VEGFA and VEGFB was higher in tumor samples with TP53 mutations.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the most predictive features of p53 status were selected based on the LASSO algorithm, and the biological correlations between these features and p53 status could also be revealed preliminarily. For example, it was reported that the microvessel count is higher in p53-mutated tumors than in p53-wildtype tumors ( Guo et al, 2008 ), as the vascular endothelial growth factor is overexpressed in p53-mutated tumors ( Riedel et al, 2000 , Uchida et al, 1998 ). Differences in microvascularity could result in differences in signal on T2 weighted images due to differences in water content ( Dang et al, 2015 ), which could explain why Maximum_6 and Median_6 are higher in p53-mutant tumors than those in p53-wildtype tumors.…”
Section: Discussionmentioning
confidence: 99%